Analisis Perawatan (Maintenance) Mesin Screw Press di Pabrik Kelapa Sawit dengan Metode Failure Mode And Effect Analysis (FMEA) di PT. XYZ - Muhammad Iqbal Pasaribu; Din Aswan Amran Ritonga; Ade Irwan (Universitas Harapan Medan, 2021)
XYZ is a palm oil mill . Produce crude palm oil (CPO) PT. XYZ have not implemented the system machine maintenance effectively, maintenance system that has been implemented is corrective maintenance that is make improvements when there is a break down. Besides that it is also assisted with planned maintenance scheduled every week for cleaning production machines. The refore it is necessary to identify the engine components who are prone to breakage (critical component) and necessary to do action maintenance specifically against critical components engine by applying maintenance schedule prediktif ( prevention) simulation technique, often know as estimate reliability using a random sampling scenario failure mode and effects (FMEA) defined as a process used to deter mine action to be done to guarantee each item physical or system can go well according to the function performed by its usersthen basedon data processing, replacement, inspection of turn filter componentsone time per year with atime sixty minutes, thegear box is worn outonetime per year with a time of one hundred andtwenty minutes, leaking in the engine body as much asone a year during eighty minutes, thewire caught fire one time per year with time fifty minutes, cable having problems as much one time per year with time one hundred eighty minutes.